Annex G of the 2001 Agreement on Succession Issues: Self-executing or Not? - Vesna Crnić-Grotić; Sandra Fabijanić Gagro; Petra Perišić (Poredbeno Pomorsko Pravo)
Following the dissolution of Yugoslavia, successor States concluded in 2001 the Agreement on Succession Issues, which aimed at resolving different issues arising from the break-up of the State. Specifically, Annex G of the Agreement regulated the issue of the protection of private property and acquired rights of citizens and legal persons of ex-Yugoslavia, requiring their protection by the successor States. Before national courts of the successor States, as well as before international judicial and arbitral bodies, there has been a number of proceedings in which physical and legal persons claimed violation of their protected rights. The principal legal issue in the course of those proceedings was whether the said Annex G constituted a self-executing treaty, apt for application without any further measures being taken, or if it was a non-self-executing one, creating a legal obligation, but not being automatically applicable and justiciable in courts. The question of whether or not an agreement is self-executing depends primarily on its own provisions and their interpretation, in accordance with the 1969 Vienna Convention on the Law of Treaties. By applying the Vienna Convention and examining the relevant national and international case law, the authors conclude that Annex G is not self-executing.